2017
DOI: 10.4103/2231-0762.200703
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between salivary glucose and blood glucose and the implications of salivary factors on the oral health status in Type 2 diabetes mellitus patients

Abstract: Aims and Objectives:The purpose of this study was to estimate and assess any correlation between random capillary blood glucose (RCBG) and unstimulated whole salivary glucose (UWSG), as well as to estimate various salivary parameters, such as flow rate, pH, buffering capacity, and the influence of these factors on the oral health status in type 2 diabetes mellitus (DM).Materials and Methods:Sixty individuals suffering from type 2 DM and 40 healthy individuals in the age group of 30–60 years were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 29 publications
2
19
0
3
Order By: Relevance
“…Seven studies reported a significantly higher DMFT index among type 2 diabetics, while Lin et al reported opposite results regarding DFS. Seven studies found no statistically significant differences between groups.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Seven studies reported a significantly higher DMFT index among type 2 diabetics, while Lin et al reported opposite results regarding DFS. Seven studies found no statistically significant differences between groups.…”
Section: Resultsmentioning
confidence: 93%
“…Forty‐five articles regarding caries experience among type 1 diabetics were analyzed (Table ). Regarding type 2 diabetes 17 studies were included (Table ). Vaziri et al and Ilgüy et al evaluated type 1 and type 2 diabetics but results for each group were separately reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The saliva of diabetics with poor metabolic control shows an increase in salivary glucose concentration [34]. The correlation of glycemia with glucose concentration in saliva is still not well established, so currently it is not used to verify the degree of metabolic control and diagnosis in diabetes mellitus [35][36][37]. ATR-FTIR spectroscopy has been used as an alternative discriminatory method to others chronic diseases, due to its major advantages of being label-free and non-destructive, rapid, high-throughput, not requiring sample preparation, and cost-effective analytical method for providing details of the chemical composition and molecular structures [38,39].…”
Section: Plos Onementioning
confidence: 99%
“…In previously published studies it was proven that salivary glucose estimation has increased values in type II diabetic melitus. 6 According to previous studies, found significant differences (p<0.05) in the buffering capacity between type II DM and control groups. This can also be attributed to the hormonal and metabolic changes in diabetic patients causing altered levels of salivary buffering systems.…”
Section: Discussionmentioning
confidence: 87%